PENGARUH STORY TELLING TERHADAP TINGKAT KECEMASAN ANAK USIA PRA SEKOLAH AKIBAT HOSPITALISASI - Ni Made Dwi Rianthi; Made Ririn Sri Wulandari; Ni Made Ari Sukmandari (Jurnal Online Keperawatan Indonesia, 2022)
Children hospitalization causes anxiety at all age levels. Reducing the anxiety of children undergoing hospitalization can be done by implementing story telling therapy. This study aimed to determine the effect of story telling on anxiety level felt by felt by preschool children due to hospitalization in the Cilinaya ward of Mangusada Badung Regional Hospital.The research was carried out with pre-experimental research with the design used was a pre-test and post-test one group design. The study was conducted from September 2nd to October 2nd 2021 with a total sample of 22 respondents using consecutive sampling. Data were collected using a face anxiety scale questionnaire. Data were analyzed using the Wilcoxon test.The results of the research on anxiety before being given story telling were mostly moderate anxiety of 13 respondents (59.1%) and anxiety after being given story telling improved to mild anxiety of 13 respondents (59.1%). The analysis result showed that there was an effect storytelling on anxiety level felt by hospitalized children in the Cilinaya ward of Mangusada Badung regional hospital with p <0.001. The recommendation of this study is expected to be input for nurses to always provide storytelling therapy to children undergoing hospitalization in order to reduce anxiety.